The Effect of PQRST Strategy on Students’ Reading Comprehension in Procedure Text. - Tengo, Fadhila Muliana; Miolo, Sartin T.; Hatibie, Yunita (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to find out the significant effect in using the PQRST Strategy on students' reading comprehension in procedure text at the ninth grade of SMPN 3 Kabila. The population of this research was all students of class IX SMPN 3 Kabila which only has one class with a number of students consisting of 24 students and the sample of this research was all students in class ninth totaling 24 students. The samples were determined using a saturated sampling technique. This research used a quantitative method with a pre-experimental design one group pre-test and post-test. There are two variables in this research, the PQRST strategy as the independent variable and the students’ reading comprehension in procedure text as the dependent variable. Data collection techniques in this research used a test, namely multiple-choice tests. The results showed that the mean score of the pre-test was 11.75, and the mean score post-test was 19.38. In addition, the results of the hypothesis of this research found that tcount > ttable or 24.04 > 2.069 with the level of significance α = 0.05. It means that the hypothesis (H1) of this research is accepted. Therefore, it can be concluded that the PQRST strategy has a significant effect on students' reading comprehension in procedure texts at the ninth grade of SMPN 3 Kabila.